Economic freedom and banking development: the experiences of selected east asian countries - Soo-Wah Low,; Noor Azlan Ghazali,; Shamshubaridah Ramlee,; Rasidah Mohd Said, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This paper investigates the role of economic freedom in banking sector development using a panel data set for the period 1975-2006 in six East Asian countries, namely Singapore, Malaysia, Indonesia, Thailand, South Korea and the Philippines. We find a direct positive link between economic freedom and banking sector development for the benchmark country, Singapore and the effects of economic freedom on banking development are not common to all countries. Differential effects are observed for Malaysia and Thailand indicating that specific country factors are at work. To establish a firmer link between economic freedom and banking development, we decompose the economic freedom index into its various sub-components. We find that legal quality is the only sub-component that is positively and robustly related to all measures of banking development that we employ and that the effect for Malaysia is different from that in Singapore. This suggests that, protection of property rights and effective enforcement of contracts are critical elements in promoting banking development. A country’s legal system needs to be strengthened if banking sector is to function well. However, the extent to which legal systems need improvement differs across countries with different institutional framework